(untitled) (Biological Sciences - PJSIR, 2022)
A growth chamber experiment was carried out to determine the influence of cultivar, sowing depth and seed size on the emergence of groundnut in a drying soil. Seeds of four cultivars (Kadiri-3, Kadiri 71· I, Gangapuri and TMV -2) classified into three size grades were sown at four depths (2,4,6 and 8 em) in soil at field capacity and no water was added subsequently. Result indicated that there were considerable differences among cultivars for rate and fractional erncrgence. Gangapuri showed the greatest fractional emergence, while, TMV -2 had the fastest rate of emergence than all otherculLivars. Sowing depth had a significant inlluence on the rate and fractional emergence and as expected. seedling emergence decreased with increased depth of sowing. In general, the rate and fractional emergence of small seeds were better than those of large seeds at all sowing depths.